Are antimicrobial peptides a double‐edged sword in hidradenitis suppurativa pathophysiology?. (1st February 2022) - Schell, S.L.; Nelson, A.M.
Abstract: Linked Article: Yao et al . Br J Dermatol 2022; 186:236–244 .